1985
DOI: 10.1007/bf00925595
|View full text |Cite
|
Sign up to set email alerts
|

C-banding analysis of six species of lung flukes,Paragonimus spp. (Trematoda: Platyhelminthes), from Japan and Korea

Abstract: We examined C-banded karyotypes of six species of lung flukes from Japan and Korea; diploid and triploid Paragonimus westermani, P. miyazakii, P. ohirai, P. iloktsuenensis and P. sadoensis, with special reference to their karyotypic diversification. C-band analysis between the diploid and the triploid westermani revealed that two of three homologues of the triploid resembled those of the diploid in C-band pattern, while the remaining chromosome showed a different pattern from any species examined here. This ka… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

1987
1987
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 5 publications
0
10
0
Order By: Relevance
“…Using the conventional Giemsa staining technique, Hirai et al (1985) observed that the triploid was an allotriploid, probably induced by interspecific hybridization between the diploid P. westermani and an unknown species. In addition, they suggested that the triploid P. westermani was an independent species and synonymous with P. pulmonalis (Miyazaki, 1978).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Using the conventional Giemsa staining technique, Hirai et al (1985) observed that the triploid was an allotriploid, probably induced by interspecific hybridization between the diploid P. westermani and an unknown species. In addition, they suggested that the triploid P. westermani was an independent species and synonymous with P. pulmonalis (Miyazaki, 1978).…”
Section: Discussionmentioning
confidence: 99%
“…Only diploid forms have been found to date in southeastern countries (Malaysia, Philippines and Thailand). However, both diploid and triploid forms of P. westermani have been found in Korea (Terasaki, 1980;Hirai et al, 1985). Many studies have been focused on the origins of triploids and their relationships with diploid P. westermani, and chromosomal studies have proven to be important for evaluating competing theories with respect to the origins of triploids.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Karyotypes of two P. westermani strains revealed the existence of diploid flukes (2n = 22) in the strain of small-sized stages and triploids (3n = 33) in the other. This triploid strain was then identified as Paragonimus pulmonalis, a species which is become a synonym (Hirai et al, 1985). Diversity can enhance different forms of pathogenicity.…”
Section: Diversity Of Parasites In the Paragonimus Genusmentioning
confidence: 99%
“…Paragonimus westermani -3 n = 33 (Sakaguchi & Tada, 1976;Hirai et al, 1985), Allocreadium fasciatusi-3 n = 21 (Ramanjaneyulu & Madhavi, 1984), Apatemon minor -3 n = 30 (Petkeviciute, 1992), Diplostomum sp. -3 n = 30 (Staneviciute, 1994), Schistosoma mansoni -2 n = 24 (Hirai & LoVerde, 1989).…”
Section: Chromosomes Of Ichthyocotylurus Platycephalusmentioning
confidence: 99%